Foreign Investment and Stock Market Development in Indonesia - Siska, Elmira; Duraipandi, Oyyappan; Tio, Lina; Ameen, Ali (PT. Riset Press International, 2024)
The Indonesian capital market is growing and is significantly influenced by domestic and international macroeconomic factors. Foreign investment is one of the worldwide factors considered to affect the growth of Indonesia's capital markets. The objective of this study is to investigate the impact of foreign investor in term of Foreign Direct Investment (FDI) and Foreign Portfolio Investment (FPI) on the value of Indonesian stock market capitalization (MarCap). This study utilized a quantitative-descriptive research approach. Annual time series for 21 years starting from 2000 to 2020 of FDI, FPI, and MarCap data utilized. Data processing uses SPSS-25 which includes Classical Assumption Test, Multiple Linear Regression, Coefficient of Determination Test, and t-test. The findings of current study prove that both FDI and FPI have a favorable and statistically significant influence on the development of stock market capitalization in Indonesia. The study implies that the government must formulate regulation which encourages macroeconomic stability and appropriate policies to attract more foreign investors to participate in Indonesia and contribute to the development of the stock market.